Defining File Format Obsolescence: A Risky Journey - David Pearson; Colin Webb (International Journal of Digital Curation, 2008)
File format obsolescence is a major risk factor threatening the ongoing usefulness of digital information collections. While the preservation community has become increasingly interested in tools for assessing a wide range of risks, the National Library of Australia is developing mechanisms specifically focused on the risks of format obsolescence. The paper reports on the AONS II Project, undertaken in conjunction with the Australian Partnership for Sustainable Repositories (APSR). The project aimed to refine and develop a software tool that would automatically find and report indicators of obsolescence risks, to help repository managers decide if preservation action is needed. The paper discusses the current mismatch between this objective and the available sources of information on file formats, and emphasises the need to take account of both local and global factors in assessing risk. The paper calls for the preservation community to engage with the further development of thinking about file format obsolescence.